Strategi Guru PAUD dalam Meningkatkan Seni Tari pada Anak Usia Dini melalui Video Pembelajaran - Rosidah, Eulis; Zahro, Ifat Fatimah; Jumiatin, Dedah (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2025)
This research was motivated by the lack of interest among some students in dance at PAUD Istiqomah. Therefore, this study aims to implement dance activities that are easy and engaging for children to support their physical motor development. Various aspects can be developed through dancing, including physical motor skills, cognitive abilities, and affective domains, all of which are interconnected. Therefore, dance can serve as a medium for teaching various life values. One solution for teachers facing challenges in the field is to teach dance movements to children using instructional video media. This study aims to identify teacher strategies to enhance young children's dance skills through the use of instructional videos. The subjects of this research were Group B children aged 5–6 years and homeroom teachers at PAUD Istiqomah Bandung. Data were collected through observation, interviews, and documentation. This study employed a qualitative descriptive approach. The results of the study show an improvement in children's dance skills through teacher strategies implemented using video-based learning media. The development of children's dance abilities was watched to improve based on field observations.